342OResponse of nivolumab monotherapy in 124 Japanese patients with advanced melanoma: Interim analysis of prospective observational study (CREATIVE study). (24th November 2019) - Yamazaki, N; Takahashi, A; Namikawa, K; Takenouchi, T; Nakamura, Y; Kitano, S; Fujita, T; Kubota, K; Yamanaka, T; Kawakami, Y
Abstract: Background: Anti-PD-1 antibody nivolumab has been approved for advanced melanoma in Japan. Although there have been clinical trial reports on nivolumab treatment for advanced melanoma, real-world data on the efficacy of nivolumab in an Asian patient cohort is still lacking. The aim of this study is to obtain real-world data on the efficacy of nivolumab in Japanese patients with advanced melanoma. Methods: This prospective observational study was performed on unresectable or metastatic melanoma patients who were treated with nivolumab. Primary endpoints were response rate (RR), and overall survival (OS). The secondary endpoints were progression-free survival (PFS) and the immune-related adverse events (irAEs) ratio. Results: In total, 124 patients from 22 institutions in Japan were enrolled between Dec. 2015 and Dec. 2017. Mucosal melanoma (34%) was the most frequent subtype in this study, followed by acral lentiginous melanoma (20%), nodular melanoma (15%), superficial spreading melanoma (13%). We observed complete response (CR) in 2 (2%), partial response (PR) in 21 (17%), stable disease (SD) in 27 (22%), and progressive disease (PD) in 59 patients (47.6%) (objective RR: 19%). Use of nivolumab as first-line treatment showed a tendency toward higher response than when used as second-line treatment (objective RR, 23% vs 11%, P = 0.12). IrAEs comprised skin reactions and endocrine-related adverse effects. The median PFS in patients with skin reactions (or skin-related irAEs) was 8.61 months compared to 2.14 months without skin-related irAEs, and 8.99 months (p < 0.001) with endocrine function suppression compared to 2.14 months in the absence of endocrine-related irAEs. Conclusions: The results of this interim analysis showed a lower RR than that reported in recent phase 2 trials conducted in Japan. The differences in the proportions of melanoma subtypes, with a higher proportion of mucosal and acral melanoma, and use of nivolumab as second-line treatment will probably lead to a lower RR to nivolumab in Japan. As the results of this study showed that the occurrence of irAEs had a significant impact on therapeutic efficiency, it is critical to take appropriate measures to manage the occurrence of irAEs. Legal entity responsible for the study: The authors. Funding: This study was sponsored by Public Health Research Foundation under the funding support from Ono Pharmaceutical Co., Ltd. and Bristol-Myers Squibb K.K. Disclosure: N. Yamazaki: Honoraria (self), Honoraria (institution), Non-remunerated activity/ies: ONO Phamaceuticals; Honoraria (self), Honoraria (institution), Non-remunerated activity/ies: Bristol-Myers Squibb; Honoraria (self), Honoraria (institution), Non-remunerated activity/ies: Novartis Pharma K.K.; Honoraria (self), Honoraria (institution), Non-remunerated activity/ies: MSD K.K.; Honoraria (self), Honoraria (institution): Merck Serono Co., Ltd.; Honoraria (self): Takeda Pharmaceutical Co., Ltd. K. Namikawa: Honoraria (institution): Public Health Research Foundation; Honoraria (self): Ono Pharmaceutical; Honoraria (self): Bristol-Myers Squibb; Honoraria (self): Merck Sharp & Dohme. T. Takenouchi: Advisory / Consultancy: Ono Pharmaceutical Co., Ltd.; Advisory / Consultancy: MSD KK; Advisory / Consultancy: Chugai Pharmaceutical Co., LTD.; Advisory / Consultancy: Novartis Pharma KK. Y. Nakamura: Honoraria (self): ONO pharmaceuticals; Honoraria (self): MSD; Honoraria (self): Bristol Myers-Squibb; Honoraria (self): Novartis Pharma K.K.; Honoraria (self): Taisho Toyama Pharma; Honoraria (self): Maruho; Honoraria (self): Taiho Pharma. S. Kitano: Honoraria (self): AstraZeneca; Honoraria (self): Chugai; Honoraria (self): Pfizer; Honoraria (self): Sanofi; Honoraria (self): Nippon Kayaku; Honoraria (self): Boehringer Ingelheim; Honoraria (self): Meiji Seika Pharma; Honoraria (self): Taiho. T. Fujita: Honoraria (self): Public Health Research Foundation; Advisory / Consultancy: ONO PHARMACEUTICAL CO., LTD; Advisory / Consultancy: Bristol-Myers Squibb Company. T. Yamanaka: Honoraria (self), Honoraria (institution): Takeda; Honoraria (self), Honoraria (institution): Taiho; Honoraria (self): Boehringer Ingelheim; Honoraria (self): Chugai. Y. Kawakami: Advisory / Consultancy: Public Health Research Foundation; Advisory / Consultancy: Ono Pharmaceutical Co., LTD; Advisory / Consultancy: Bristol-Myers Squibb Company. All other authors have declared no conflicts of interest.